Venereal Diseases Treatment for Merauke’s Marind (Marind-Anim) Tribe in the Dutch Colonial Period - Rosmaida Sinaga; Hafnita Sari Dewi Lubis; Yushar Tanjung; Lister Eva Simangunsong (IHiS (Indonesian Historical Studies))
This article provides some proofs that influenced the increasing number of Marind-Anim people who suffering from venereal diseases. It also provides factual efforts that had been done by the colonial government as well as Catholic missionaries in Merauke to overcome this problem. This study applies historical methods with four stages: heuristics, verification (internal and external criticism), interpretation/explanation and historiography. Primary sources obtained from National Archives of the Republic of Indonesia i.e., Memorie van Overgave van het Bestuur over de Afdeeling Zuid Nieuw Guinea; letter of the Minister of Colonies to the Governor General of the Dutch East Indies; Report of Assistant Resident Zuid Afdeeling Nieuw Guinea to the Director of Government; and official printed sources, e.g., Volkstelling 1930. Michel Foucault's power relations theory is used to analyze the causes of venereal disease in the Marind Tribe. The results shows that the cause of the increasing number patients who had venereal disease in the Marind tribe, Merauke, was related to their traditional understanding which legalized free sex and deviant sexual activities in the Marind tribe. The imbalanced power relations between men and their wives and between men and adolescence men causing venereal diseases and sexual perversions in the Marind Tribe. The strategy implemented by the colonial government was to involve Catholic missionaries who were trusted to overcome the disease by building a housing model that can only be occupied by nuclear families who are not infected with venereal diseases. The colonial government demolished men’s houses because there were possibilities of homosexual intercourses which become one of the causes of venereal disease among the Marind Tribe. In addition, the government required the cenderawasih bird hunterers to have their genital health checked as a hunting permit. The government built hospitals and clinics and invented doctors who specialize in venereal disease to treat the patients. These strategies has succeeded in treating and eradicating venereal diseases among the Marind Tribe.